SAT0255 Clinical and Radiographic Outcomes at 2 Years and the Effect of TOCILIZUMAB Discontinuation following Sustained Remission in the Second and Third Year of the ACT-RAY Study. (10th June 2014) - Huizinga, T.W.; Conaghan, P.G.; Martin-Mola, E.; Schett, G.; Amital, H.; Xavier, R.M.; Troum, O.; Aassi, M.; Bernasconi, C.; Dougados, M.
Abstract : Background: In ACT-RAY, MTX-IR patients (pts) with moderate to severe RA were randomized to either an add-on (tocilizumab [TCZ]+MTX) or a switch (TCZ+placebo [PBO]) strategy. Data at 24 and 52 weeks demonstrated clinical and radiographic benefit without clinically meaningful differences between the 2 arms for most endpoints. 1, 2 During years 2 and 3, the protocol included a step-down strategy with the goal of achieving drug-free remission (discontinuation of study drugs while DAS28 remained <2.6). Objectives: To compare the safety and efficacy of TCZ-based treatment strategies, to evaluate the treat-to-target (T2T) approach and to assess the course of disease activity in pts who discontinued TCZ due to sustained remission. Methods: ACT-RAY was a phase 3b trial. Pts on stable doses of MTX were randomized to either add TCZ 8 mg/kg IV every 4 weeks or switch to TCZ 8 mg/kg IV with oral PBO. Using a T2T approach, DMARDs other than MTX were added from Week 24 if DAS28>3.2, while maintaining MTX/PBO blinding. Between Weeks 52-104, pts in sustained clinical remission (DAS28<2.6 at 2 consecutive visits 12 weeks apart) discontinued TCZ and were followed up every 4 weeks for 1 year. If sustained remission was maintained, added DMARDs and then MTX/PBO were discontinued. In case of flare, defined at the investigator's discretion, the last effective treatment or TCZ with blinded MTX/PBO was restarted. Results: Pt baseline (BL) data were similar between treatment arms except for higher mean Genant-Sharp Scores in the switch group. Of the 556 randomized pts, 423 (222 add-on, 201 switch) completed year 2 and 100 (52 add-on, 48 switch) extended into year 3. Reasons for withdrawal included lack of efficacy (1.8% add-on, 5.1% switch) and adverse events (AEs; 10.1% add-on, 11.6% switch, including 4 and 6 deaths, respectively). Of pts entering into year 2, ∼50% discontinued TCZ after achieving sustained remission and some further stopped other study treatments. Most pts (84.0%) had a subsequent flare, but responded well to TCZ reintroduction (after a median of 90 days). Only a small minority of pts who completed Week 52 (5.9%) achieved drug-free remission. Despite many pts stopping TCZ for some period, radiographic progression was minimal in both groups, with differences favoring add-on pts. SAEs and serious infections per 100 PY were 12.2 and 4.4, respectively, for add-on pts and 15.0 and 3.7, respectively, for switch pts. In pts with normal BL values, ALT elevations >3x ULN were more frequent in add-on pts vs switch pts (14.3% vs 5.4%). Conclusions: Efficacy and safety of TCZ+MTX and TCZ+PBO strategies were comparable, but small differences favored combination therapy. T2T strategies could be successfully implemented with TCZ to achieve sustained remission, after which TCZ was stopped. Biologic-free remission was maintained for a limited time, but most pts eventually flared. TCZ restart led to rapid improvement. References: Dougados M, et al. Ann Rheum Dis. 2013;72:43-50. Dougados M, et al. Ann Rheum Dis. 2014. In Press. Disclosure of Interest: T. Huizinga Consultant for: Abbott, Axis Shield Diagnostics, Biotest AG, BMS, Crescendo Bioscience, Novartis, Pfizer, Roche, Schering-Plough, UCB and Wyeth., P. Conaghan Speakers bureau: BMS, Janssen, Pfizer and Roche., E. Martin-Mola: None declared, G. Schett: None declared, H. Amital: None declared, R. Xavier Consultant for: Merck, Pfizer and Roche., O. Troum Grant/research support: ACT-RAY clinical trial., M. Aassi Employee of: F. Hoffman-La Roche Ltd., C. Bernasconi Consultant for: F. Hoffman-La Roche Ltd., M. Dougados Consultant for: Abbott, Pfizer, Roche and UCB. DOI: 10.1136/annrheumdis-2014-eular.1434